1991
DOI: 10.1002/ar.1092290115
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural changes of rat plantaris motoneurons following compensatory hypertrophy of the muscle

Abstract: The conduction velocity and histological structure of motoneurons innervating normal and hypertrophied rat plantaris muscles were investigated. Hypertrophy was produced by ablation of synergist muscles. Single motor units were obtained by ventral root dissection and conduction velocities measured. The structure of neurons was investigated following retrograde labeling with horseradish peroxidase. A combined silver, gold and cholinesterase staining method was developed to study the motor endplate. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Adaptations on the part of the fast motoneurons were accompanied by an increased mean cell capacitance, suggesting an increase in soma volume. Previous investigations on motoneuron adaptations to increased activity have found either no change34, 43, 44 or a decrease12 in histologically measured cell size. Nonetheless, in the present study, mean input resistance and rheobase were not influenced by activity, in spite of apparent changes in cell capacitance (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Adaptations on the part of the fast motoneurons were accompanied by an increased mean cell capacitance, suggesting an increase in soma volume. Previous investigations on motoneuron adaptations to increased activity have found either no change34, 43, 44 or a decrease12 in histologically measured cell size. Nonetheless, in the present study, mean input resistance and rheobase were not influenced by activity, in spite of apparent changes in cell capacitance (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies evaluating motoneuron size in response to compensatory overload have provided contradictory results. Finkelstein et al (1991) indicated decreased motoneuronal soma size following muscle hypertrophy in plantaris motoneurons, but in research of Roy et al (1999) the mean motoneuron soma area was not affected after functional overload of the same muscle.…”
Section: Discussionmentioning
confidence: 90%
“…The shift to slower muscle characteristics in the hypertrophied PLA muscle has also been reported by other investigators. Thus, a slower velocity of shortening (Binkhorst and Van'tHof, 1973;, reduction of conduction velocity of motoneuron with reduced cell body size (Finkelstein et al, 1991), reduction of biochemically measured myosin Noble et al, 1983) and myofibrillar ATPase activity (Baldwin et al, 1977Tsika et al, 1987) have been described. In present study, the twitch and tetanus of the OP and CON-L muscles shifted to a slow muscle pattern in a manner similar to these reports ( Figs.…”
Section: Discussionmentioning
confidence: 99%